Thymidine Phosphorylase Is Increased in COVID-19 Patients in an Acuity-Dependent Manner - Li, Wei; Yue, Hong (Frontiers in Medicine, 2021)
Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-COV-2), is a human respiratory disease. Hitherto, there is no effective treatment has been established. Patients with cardiovascular or diabetes comorbidities are a high-risk cohort. COVID-19 is accompanied by excessive systemic thrombotic events, but the mechanism is not yet known. Recent studies have indicated that thymidine phosphorylase (TYMP) plays an important role in platelet activation, thrombosis, and TYMP expression is increased in diabetic patients. By using data provided by the MGH (Massachusetts General Hospital) Emergency Department COVID-19 Cohort with Olink Proteomics, here we show that plasma TYMP level is correlated with the COVID-19 associated thrombotic event, inflammation, and organ damage, as evidenced by the positive correlations with plasma D-dimer, CRP (C reactive protein), and LDH (lactate dehydrogenase), as well as Interferons (IFN). Plasma TYMP is also positively correlated with COVID-19 patients who had respiratory symptoms. TYMP thus could be an acuity marker for COVID-19 diagnosis. Targeting TYMP with tipiracil, a selective TYMP inhibitor, which has been approved by the Food and Drug Administration for clinical use, could be a novel effective medicine for COVID-19.